Efficacy and safety of inclisiran in patients with established cerebrovascular disease: pooled, post hoc analysis of the ORION-9, ORION-10 and ORION-11, phase 3 randomised clinical trials. (14th October 2021) - Koenig, W; Ray, K K; Kallend, D G; Landmesser, U; Leiter, L A; Schwartz, G G; Wright, R S; Garcia Conde, L; Jaros, M; Raal, F J
Abstract: Background: Patients (pts) with hyperlipidaemia and established cerebrovascular disease (CeVD) are at an increased risk of future strokes or other cardiovascular events.[1] In ischaemic stroke survivors, statins and inhibitors of proprotein convertase subtilisin-kexin type 9 (PCSK9) reduce recurrent cardiovascular events including stroke.[2–4] With guidelines increasingly advocating lower LDL-C goals, add-on lipid lowering therapies to statins may be needed. Inclisiran, a first-in-class small interfering RNA (siRNA) targeting PCSK9 messenger RNA, when added to maximally tolerated statin therapy, may provide further LDL-C lowering with a convenient, infrequent dosing schedule in pts with established CeVD. Purpose: To assess efficacy and safety of inclisiran in pts with established CeVD. Methods: Pts with HeFH, ASCVD or its risk equivalents from ORION-9 (NCT03397121]), ORION-10 (NCT03399370), and ORION-11 (NCT03400800) were randomised 1:1 to receive inclisiran sodium 300 mg (equivalent to 284 mg inclisiran) or placebo (pbo) at Days 1, 90 and 6-monthly thereafter to Day 540. This post hoc analysis included pts with established CeVD (ischaemic stroke, and/or carotid artery stenosis by angiography or ultrasound >70%, and/or prior percutaneous or surgical carotid artery revascularisation). Percentage LDL-C change from baseline to Day 510 and corresponding time-averaged percentage change from baseline after Day 90 to Day 540 were evaluated. Safety was assessed over 540 days. Results: Of 202 pts with established CeVD, 110 and 92 received inclisiran and pbo, respectively. At baseline, 90.0% (99/110) of pts in inclisiran and 84.8% (78/92) in pbo group reported prior ischaemic stroke(s); others had carotid artery stenosis and/or carotid revascularisation (Table 1). Mean (95% CI) pbo-corrected LDL-C percentage change from baseline at Day 510 with inclisiran was −55.2% (−64.5 to −45.9); corresponding time-averaged change from baseline after Day 90 to Day 540 was −55.2% (−62.4 to −47.9) (P<0.0001 for each; Table 2). Treatment-emergent adverse event (TEAE) and treatment-emergent serious adverse event (TESAE) were more frequent in the inclisiran vs pbo group but were consistent with the overall pooled (N=3655) population of the combined trials. Clinically relevant TEAEs at the injection site were reported more frequently with inclisiran (3.6% [4/110]) vs pbo (0% [0/92]), but none were severe. Percentage of pts with clinically relevant laboratory measurements was low and similar between treatment groups and consistent with the overall pooled population (Table 2). Conclusions: In pts with established CeVD, a twice-yearly dosing with inclisiran (after the initial and 3-month doses) provided sustained additional LDL-C reduction of ∼55%. A modest excess of mild/moderate TEAEs at the injection site were reported with inclisiran. The cardiovascular benefits of inclisiran among patients with established CeVD are being evaluated in ongoing trials. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novartis Pharma AG, Basel, Switzerland.